PENGARUH PENGGUNAAN WIND GATE TERHADAP UNJUK KERJA TURBIN ANGIN DARRIEUS TIPE H - Lia Agustina; I Made Susanto; I Wayan Wawan Mariki (Scientific Journal of Mechanical Engineering Kinematika, 2022)
Has performed characterization of the darrieus wind turbine type H through wind speed measurement and rotor rotation speed which can be used to knowing the optimal performance wind turbine. Measurement of wind speed is done with using an anemometer. Measurement of rotor rotation speed using a tachometer. Wind turbines characterized in this study are darrieus wind turbines type H varied into wind turbines using wind gates and wind turbines without wind gates. The results obtained from this study are differences power values and differences in the efficiency values of the wind turbine using the wind gate and without the wind gate. The maximum power value of wind turbines is owned by the darrieus wind turbine type H without using a wind gate which reaches 77.55 watts of power. The highest efficiency value is owned by darrieus wind turbines type H using the wind gate which reaches 36.25%.